REKONDISI SISTEM PENGAPIAN DAN PENGISIAN MESIN TOYOTA KIJANG 5K - , DWI FAJAR NUGROHO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
As one graduation requisite so every student must be last project. The writer takes subject to repair ignition system and charging system engine trainer Toyota Kijang 5K. Beside graduation requisite, the writer hopes the engine trainer can use for knowlege and practice so this project can usefull for student learning. In the last project, the writer repair engine and electricalâs system with overhaul engine, check all condition parts on engine, check all condition of electricalâs parts they are ignition system component, charging system component, starting system component, and than compare result with component size standart so the writer can detect broken parts that have to replace. The result of the last project, engine trainer can use again with good condition. Students can be understand the working principle of the ignition system and charging system on engine Toyota Kijang 5K, therefor the writer expected the engine trainer will be useful for student who will learn more about wiring ignition system and charging system on the engine trainer.